CONCEPTION AND USAGE OF CONCEPTS OF RARE BOOK, VALUABLE BOOK AND OLD BOOK IN BOOK CULTURE OF SOVIET LITHUANIA - LIEPAITĖ, INGA (Knygotyra, 2011)
The aim of the study was to ascertain how the concepts of rare book, valuable book and old book functioned in the book culture of Soviet Lithuania. Two standpoints have been adopted as a basis for revealing the peculiarities of the conception and usage of these concepts: 1) the conception of Lithuanian bibliophily in the occupation period; 2) the practical work of bibliographers, librarians and researchers in preparing the national retrospective bibliography. Officially, there were two dominant attitudes towards bibliophily in Soviet Lithuania. In the broad sense, traditions of elite bibliophily, developed in Lithuania in the interwar period, were rejected, and the strained interpretation of bibliophily as mass / socialistic / real bibliophily came into use, which was the merest liking of books, or a hobby (positive view); bibliophily itself in the narrow sense was interpreted as collecting rare and valuable books and identified with bibliomania or elite bibliophily (negative view). In the latter case, the concepts of rare book and valuable book first of all were identified with old and expensive books; in case of mass bibliophily, these concepts meant deficit of books, which emerged because of an increasing demand for new books. It should be noted that the concepts of rare book, valuable book and old book were not analyzed on the theoretical level, and the classification of old Lithuanian books in the occupation period was not applied, either. Such concepts as a rarity or very rare book were used only as synonyms of the concept of rare book. The concepts of rare book, valuable book and old book were used by bibliographers most often alternately, i.e. an old book was named in the same breath as a rare and valuable book. The sore point was the periodization of the retrospective bibliography Books in Lithuanian among bibliographers. According to the archival material, the following dates of the end of the old rare Lithuanian book were suggested: 1) 1800, 2) 1825, 3) 1861, and 4) 1863. The year 1861 was chosen as the date related to the manifest on the abolition of serfdom, promulgated by the tzarist Russia in that year.